Pengaruh Pembelajaran Inkuiri Terbimbing Terhadap Kemampuan Komunikasai Matematis Siswa Sekolah Menengah Pertama - Samsidar, Windi; Coesamin, M; Bharata, Haninda (FKIP Universitas Lampung, 2018)
The Influence of Guided Inquiry Learning Towards Student’s Mathematical Communication Skill Junior High School. This quasi experimental research aimed to find out the influence of guided inquiry learning model towards student’s matemathical communication skill. The population of this research was all of eight grade students of SMPN 9 Bandarlampung in academic year of 2018/2019 as many as 180 students that were distributed into 6 classes. The samples of this research were students of VIIIA as many as 29 students and VIIIC as many as 29 students class that were chosen by purposive sampling technique. The design of this reserch was the pretest-postest control group design. The analysis data which used was mann-whitney test. The data in this research was quantitaive data that obtained by student’s mathematical communication scale. The Analysis data by using mann whitney test is obtained that guided inquiry learning model influenced student’s mathematical communication skill. Keywords: guided inquiry, mathematical communication, the influenceDOI: http://dx.doi.org/10.23960/jpmipa/v19i1.pp13-24